Challenges before victims' protection in Bulgaria in view of harmonising protection frameworks throughout the European Union - Ilcheva, Miryana; Markov, Dimitar; Yordanowa, Maria (My University, 2014)
In conclusion, as witnessed by the overview of problematic areas of victim protection in Bulgaria, the situation of victims is a clear reflection of many of the general challenges before the country’s criminal justice system as a whole. The use of electronic tools, the co-ordination among institutions and their co-operation with the civic sector are indispensable components of every EU Member State’s modern criminal policy and have to be implemented by both normative and policy steps. In this sense, Bulgarian authorities and NGOs involved have to, like their counterparts throughout Europe, re-define the balance between the entitlements of the defendant and those of the victim and work on both in their correlation to achieve efficient and effective functioning of criminal justice and the higher trust of the general public.
Keywords: victims’ protection in Bulgaria